P3_2 Stunning weapons - Perry, Michael; Bettles, John; Pilkington, Nathan; Clarke, Iain (Physics Special Topics, 2011)
Â  The non-lethal apprehension of criminals is an issue of ever increasing importance for law enforcement the world over, existing means are primarily single use due to the need for wires to transmit the discharge to the target. This paper aims to establish the viability of a wireless means of transmitting the electrical discharge of a stun gun through a process of high voltage discharge. The maximum potential range over which the necessary discharge could be projected was found to be 15cm, this while low could have practical application.